Identification of Students’ Misconception in The Topic of Population using Four-Tier Diagnostic Test - Sandika, Bayu (Universitas Negeri Surabaya, 2020)
This study aims at identifying the students' misconception in the topic of population using four-tier diagnostic test. This research was conducted on the lecture of Basic Ecology toward 30 students of Biology Education, IAIN Jember as the subjects. Data were collected using a four-tier diagnostic test then analyzed using a descriptive method. Findings of the study indicate that students' misconception reached 32.8%. It can be concluded that students' misconception in the topic of the population was moderate.